Transgenic cotton-fed Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) affects the parasitoid encarsia desantisi Viggiani (Hymenoptera: Aphelinidae) development - Pessoa, R. [UNESP]; Rossi, G. D. [UNESP]; Busoli, A. C. [UNESP] (Springer, 2015)
Cotton cultivars expressing Cry proteins are widely used to control lepidopteran pests. The effects of transgenic plants containing insecticidal Cry proteins on non-target species must be comprehended for a better and rational use of this technology for pest management. We investigated the influence of the Bt cotton cultivars NuOPAL and FM 975 on biological parameters of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), a non-target pest of Bt cotton cultivars and on its parasitoid Encarsia desantisi Viggiani (Hymenoptera: Aphelinidae). The experiments were conducted in a climatized room, and the non-transgenic near isolines were used for rearing whiteflies as control hosts. The effects of the Bt cotton cultivars on the period of embryonic and larval development and the percentage of adult emergence of B. tabaci were assessed. The period required for embryonic, larval, and pupal development and the percentage of emergence and longevity of E. desantisi females were determined using Bt cotton-fed and non-Bt cotton-fed B. tabaci as hosts. Both Bt cotton cultivars resulted in a decrease of approximately 20% of adult emergence of B. tabaci. Differently, an increase of approximately 10% of adult emergence of E. desantisi was observed for parasitoids that used hosts fed with both Bt cotton cultivars. However, female parasitoid longevity decreased when their hosts were fed on Bt cotton cultivars. Our data suggest that the use of Bt cotton cultivars in association with the biological control agent E. desantisi could be functional for the management of B. tabaci in Bt cotton crops.
Keywords: Biological control; Indirect effects; Integrated pest management; Non-target species; Risk assessment; Transgenic crops